2001
DOI: 10.1080/07315724.2001.10719162
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Leptin Resistance on Acute Fuel Metabolism after a High Carbohydrate Load in Lean and Overweight Young Men

Abstract: Objective: Six lean (BMI ϭ 20.8 Ϯ 0.7) and seven overweight (BMI ϭ 30.8 Ϯ 1.7) young men (18 -27 years old) were studied to investigate the acute effect of a high-carbohydrate meal on leptin levels and its relation to energy expenditure as well as to protein, carbohydrate and fat oxidation.Methods: Study participants were given a high-carbohydrate meal (17% as protein, 80% as carbohydrates and 3% as lipids) covering 40% of their estimated daily energy requirements. Serum leptin, insulin, glucose, free fatty ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
2

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 39 publications
0
5
0
2
Order By: Relevance
“…In addition, the reduced Epi and NE and the absent dopamine response to exercise in obese subjects suggested the possibility of a centrally mediated attenuation of hypothalamic-pituitary-adrenal axis and/or sympathetic adrenal-medullary function. It is possible that the blunted GH and catecholamine response to exercise leads to reduced carbohydrate and fat utilization during exercise (5,6) and, as a result, to a greater protein utilization (26). Consistent with this, previous studies have demonstrated that elevated BMI was associated with a reduced training effect in children and adolescents, following a prolonged resistance training intervention (13).…”
Section: Discussionmentioning
confidence: 67%
“…In addition, the reduced Epi and NE and the absent dopamine response to exercise in obese subjects suggested the possibility of a centrally mediated attenuation of hypothalamic-pituitary-adrenal axis and/or sympathetic adrenal-medullary function. It is possible that the blunted GH and catecholamine response to exercise leads to reduced carbohydrate and fat utilization during exercise (5,6) and, as a result, to a greater protein utilization (26). Consistent with this, previous studies have demonstrated that elevated BMI was associated with a reduced training effect in children and adolescents, following a prolonged resistance training intervention (13).…”
Section: Discussionmentioning
confidence: 67%
“…However, we previously demonstrated that the growth hormone and cate‐cholamine response to exercise is attenuated and the dopamine response is almost completely blunted in obese compared with normal weight children and adolescents (25). Therefore, we can only hypothesize that the blunted growth hormone and catecholamine response and the absence of dopamine response to exercise lead to reduced carbohydrate and fat utilization during exercise (26,27), and as a result to a greater protein utilization (28). Increased protein utilization may explain why previous resistance training studies in children demonstrated that elevated BMI was associated with reduced training effect on muscle mass and strength (29).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding carbohydrate consumption, data are somewhat conflicting. While high glycemic index carbohydrate consumption or drastic high-carbohydrate diet (80% carbohydrate) may lead to leptin resistance ( 6 , 7 ), different high-carbohydrate diets have no or the opposite effects on leptin sensitivity and blood concentrations ( 8 , 9 ). On the other hand, fat intake has consistently been proven to be associated with a leptin resistance state ( 10 , 11 ).…”
Section: Introductionmentioning
confidence: 99%